Big data, big innovation : enabling competitive differentiation through business analytics - Stubbs, Evan. (Hoboken, New Jersey : Wiley, 2014)
"A practical guide to leveraging your data to spur innovation and growth. Your business generates reams of data, but what do you do with it? Reporting is only the beginning. Your data holds the key to innovation and growth - you just need the proper analytics. In Big Data, Big Innovation: Enabling Competitive Differentiation Through Business Analytics, author Evan Stubbs explores the potential gold hiding in your un-mined data. As Chief Analytics Officer for SAS Australia/New Zealand, Stubbs brings an industry insider's perspective to guide you through pattern recognition, analysis, and implementation. Big Data, Big Innovation: Enabling Competitive Differentiation Through Business Analytics details a groundbreaking approach to ensuring your company's upward trajectory. Use this guide to leverage your customer information, financial reports, performance metrics, and more to build a rock-solid foundation for future growth. Build an effective analytics team, and empower them with the right tools Learn how big data drives both evolutionary and revolutionary innovation, and who should be responsible Identify data collection and analysis opportunities and implement action plans Design the platform that suits your company's current and future needs Quantify performance with statistics, programming, and research for a more complete picture of operations Effective management means combining data, people, and analytics to create a synergistic force for innovation and growth. If you want your company to move forward with confidence, Big Data, Big Innovation: Enabling Competitive Differentiation Through Business Analytics can show you how to use what you already have and acquire what you need to succeed"--
Machine generated contents note: Preface Acknowledgments PART ONE May You Live in Interesting Times CHAPTER 1 Lead or Get Out of the Way The Future is Now The Secret is Leadership Notes CHAPTER 2 Disruption as a Way of Life The Age of Uncertainty The Emergence of Big Data Rise of the Ronin The Knowledge Rush Systematized Chaos Notes PART TWO Understanding Culture and Capability CHAPTER 3 The Cultural Imperative Level 1: Dazed and Confused Level 2: Activities and Algorithms Level 3: Value and Outcomes Level 4: Functional Innovation Level 5: Revolutionary Disruptor Notes CHAPTER 4 The Intelligent Enterprise Level 1: Unstructured Chaos Level 2: Structured Chaos Levels 3 -- 5: The Intelligent Enterprise Notes PART THREE Making It Real CHAPTER 5 Organizational Design What Should It Look Like? What Should It Focus On? What Services Can It Offer? What Data Does It Need? Notes CHAPTER 6 Operating Models What's the Goal? What's the Enabler? How Does It Create Value? The Wheel of Value Ensuring Sustainability Notes CHAPTER 7 Human Capital What Capabilities Do I Need? How Do I Get the Right People? How Do I Keep Them? Notes PART FOUR Making it Happen CHAPTER 8 Innovating with Dynamic Value The Innovation Cycle The Innovation Paradox The Secret to Success: Dynamic Value The Innovation Engine Reinventing the R?nin Notes CHAPTER 9 Creating a Plan Start the Conversation Defining the Vision Identifying Opportunities Mapping Responsibilities Taking to the Next Level Notes CHAPTER 10 The Final Chapter Is Up to You Glossary About the Author Index.
Includes index.
Includes bibliographical references and index.
Print version record and CIP data provided by publisher.
Keywords: Business planning; Strategic planning; Big data; Decision making -- Statistical methods; Industrial management -- Statistical methods; BUSINESS & ECONOMICS -- General; Big data; Business planning; Decision making -- Statistical methods; Industrial management -- Statistical methods; Strategic planning; Electronic books; Electronic books